2015
DOI: 10.1371/journal.pone.0125127
|View full text |Cite
|
Sign up to set email alerts
|

Common Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) Epitopes Mediate Multiple Routes for Internalization and Function

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a soluble protein that directs membrane-bound receptors to lysosomes for degradation. In the most studied example of this, PCSK9 binding leads to the degradation of low density lipoprotein receptor (LDLR), significantly affecting circulating LDL-C levels. The mechanism mediating this degradation, however, is not completely understood. We show here that LDLR facilitates PCSK9 interactions with amyloid precursor like protein 2 (APLP2) at neutral pH leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Importantly, mAbs LY and AM in complex with PCSK9 bound to APLP2 in an ELISA-based assay and the addition of furin reduced the binding of LY but not AM (K. M. Schroeder, unpublished observations). Our preliminary fi ndings support the hypothesis proposed by DeVay and coworkers ( 34,35 ) that APLP2 mediates the CL of anti-PCSK9 antibodies that are bound to PCSK9. We are pursuing the hypothesis that LY avoids the APLP2-dependent, antigen-mediated CL pathway by permitting the proteolytic cleavage of PCSK9.…”
Section: Proteolytic Cleavage Of Pcsk9 Slows the CL Of Ly From Serumsupporting
confidence: 90%
See 3 more Smart Citations
“…Importantly, mAbs LY and AM in complex with PCSK9 bound to APLP2 in an ELISA-based assay and the addition of furin reduced the binding of LY but not AM (K. M. Schroeder, unpublished observations). Our preliminary fi ndings support the hypothesis proposed by DeVay and coworkers ( 34,35 ) that APLP2 mediates the CL of anti-PCSK9 antibodies that are bound to PCSK9. We are pursuing the hypothesis that LY avoids the APLP2-dependent, antigen-mediated CL pathway by permitting the proteolytic cleavage of PCSK9.…”
Section: Proteolytic Cleavage Of Pcsk9 Slows the CL Of Ly From Serumsupporting
confidence: 90%
“…The fi nding of DeVay and coworkers ( 34,35 ) of most relevance to our work was that an anti-PCSK9 antibody was transported with PCSK9 to lysosomes by the APLP2-mediated pathway. Our preliminary studies confi rmed that PCSK9 binds via its C-terminal domain to APLP2 at acidic pH (K. M. Schroeder, unpublished observations).…”
Section: Proteolytic Cleavage Of Pcsk9 Slows the CL Of Ly From Serummentioning
confidence: 66%
See 2 more Smart Citations
“…This suggested that PCSK9 can divert LDLR to lysosomes from the luminal side of the membrane via its Cys-His-rich domain interaction with APLP2 (31). Recent evidence also showed that the LDLR forms a complex with APLP2 at the cell surface (32). This finding was not unprecedented, as APLP2 is involved in the transport of transmembrane proteins such as MHC class I molecules to lysosomes (33,34).…”
mentioning
confidence: 99%